PENATALAKSANAAN FISIOTERAPI KASUS BELL’S PALSY SINISTRA DENGAN MODALITAS LOW LEVEL LASER TERAPY, MASSAGE DAN PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION FACIAL - Sirojuddin, Dzulfiqar Hendry; Jaleha, Boki (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Bell's Palsy is an acute paralysis that occurs in the facial nerve with an unknown cause. This condition is relatively common and can affect facial muscle function, leading to functional limitations in daily activities. Objective: This study aims to describe the application and potential effectiveness of physiotherapy interventions, including low-level laser therapy, massage, and Proprioceptive Neuromuscular Facilitation (PNF), in managing Bell’s Palsy sinistra. Method: This study uses a case study approach focusing on a patient with Bell’s Palsy sinistra. Physiotherapy interventions applied include low-level laser therapy, massage, and facial PNF techniques administered progressively. Result: Low-level laser therapy helps accelerate the wound healing process, improve tissue repair and remodeling, restore normal nerve function after nerve injury, reduce pain, stimulate endorphin release, and modulate the immune system. Massage and facial PNF techniques contribute to improving muscle strength and endurance, facilitating stability, mobility, neuromuscular control, and coordinated movements, thereby supporting the recovery of muscle function. Conclusion: The combination of low-level laser therapy, massage, and facial PNF shows potential benefits in improving facial muscle function in patients with Bell’s Palsy. This case is relevant due to the high incidence of the condition and the unclear etiology, highlighting the importance of effective physiotherapy management.